Mesotherapy with Snake Venom Pharmacopuncture to Treat Hand Eczema: Two Cases Report - Sungha Kim; Jinbok Lee; Minseop Shin (Korean Pharmacopuncture Institute, 2020)
Hand eczema is a recurrent and resistant disease that seriously affects the quality of life of patients; currently, there are no ideal treatments for hand eczema. Here, we describe two patients who presented with hand eczema to illustrate the potential efficacy of mesotherapy with snake venom pharmacopuncture (SVP). A 23-year-old woman (Case 1) and a 47-year-old woman (Case 2) presented to the clinic with symptoms of pruritic rash, blis-ters, and itchiness on both the hands and the left hand, respectively. Both patients were diagnosed with hand eczema based on the physical examination of blisters and redness only on the hands. The patients underwent 1 month (Case 1) and 1 week (Case 2) of mesotherapy with SVP. After treatment, the lesions completely improved and did not recur at 1 year of follow-up. These outcomes suggest that mesotherapy with SVP may be effective for the resolution of hand eczema; however, further research is needed to confirm these findings.